Tryptophan fluorescence quenching as a monitor for the protein conformation changes occurring during the photocycle of bacteriorhodopsin under different perturbations. - Jang, D J (1989)
The rates of the quenching and recovery of tryptophan fluorescence are determined in the microsecond-millisecond time scale during the photocycle of bacteriorhodopsin under different perturbations. The kinetics suggest the presence of two quenching processes, a rapid one (on the time scale of photocycle intermediate L550 formation or faster) and a slow one (slightly slower than the slow component of intermediate M412 formation). The slow quenching process is found to respond to different perturbations in the same manner as the slow component of M412 formation. It has the same activation energy, it is inhibited if metal cations are removed, it is negligible at pH values greater than the pKa of tyrosine, and its rate is slowed down when 75% of the lipids are removed. These results, together with the observed value of the quenching activation energy, suggest that the rates of the tryptophan fluorescence quenching, like those of tyrosinate and M412 formations during the cycle, are all determined by the rates of the protein conformation changes. The pH studies of the slow quenching process show that the maximum quenching probability occurs at neutral pH. A rapid decrease in quenching occurs at lower pH (approximately 3 and approximately 5.5) and higher pH (approximately 9). Two quenching mechanisms involving energy transfer to either retinal or to tyrosinate are considered. Protein conformation changes resulting from a change in the ionization state of amino acids of different pKa values could change the tryptophan-retinal (or tryptophan-tyrosinate) coupling and thus the quenching efficiency.